KEKERASAN DALAM "˜PERSAHABATAN BERACUN' ANTARPEREMPUAN PADA NOVEL ANTí‰CHRISTA KARYA AMí‰LIE NOTHOMB - Intan, Tania; Hasanah, Ferli; Wardiani, Sri Rijati (Diksi, 2021)
(Title: Violence in Toxic Friendship Between Women in Amélie Nothomb's "Antéchrista" Novel). Violence is often identified with masculine expressions inherent in men. However, in reality, it is not gender-exclusive because women are also enabled to do so, including against those closest to them such as friends, as revealed in the novel Antéchrista by Amélie Nothomb, a Belgian francophone writer. This study aims to examine how the theme of violence in the 'toxic friendship' between women is displayed in the novel. The method used is descriptive qualitative with a feminist literary criticism approach. The data were collected from the novel using the note-taking technique and analyzed using the content analysis technique. The data consisting of words, phrases, and sentences in French were then translated by the researchers to be classified, interpreted, and studied. The result of the research shows that the novel Antéchrista presents women as victims who are also perpetrators of violence through oppression against each other, motivated by jealousy and intrasexual competition. The form of violence is in the form of psychological and verbal which is manifested in the form of intimidation, humiliation, and ostracism. Keywords: opression, toxic friendship, resistensi, women, feminist literature criticism